Honckenya peploides: Regional Gene Diversity and Global Karyotype Investigations - Sigurður Halldór Árnason 1980- (2014)
Integration of classical ecological measurements with molecular, cytogenetic and statistical analysis techniques is vital to a greater understanding of ecological and evolutionary relationships in time and space. Such understanding is the key to re-assembling and rehabilitating diversity in the face of current environmental and climate changes. In this study, molecular and cytogenetic techniques were used to evaluate both levels of genetic diversity and differentiation as well as karyotype diversity in Honckenya peploides. Populations from Surtsey were studied using Amplified Fragment Length Polymorphisms (AFLP) and diversity measures were compared to populations from other regions including the island Heimaey, the southern coast of Iceland, Greenland and Denmark. Main results include: (i) Surtsey has the highest proportion of polymorphic markers as well as a comparatively high genetic diversity and Denmark the lowest, possibly indicating that H. peploides populations on Surtsey originate from multiple colonization events from several source locations; (ii) the total genetic differentiation (FST) among Surtsey and Heimaey populations was significant and less than half of that found among mainland Iceland populations, indicating significant gene flow within the islands; (iii) significant genetic distance was found within Surtsey, among sites, this appears to correlate with the age of plant colonization; iv) most genetic variation was found within localities, possibly due to the outcrossing and subdioecious nature of the species; and (v) there is a positive and significant association between genetic differentiation and geographic distance at the broad scale indicating isolation by distance has an effect on the Surtsey and Icelandic populations. Through collaboration with investigators worldwide, seeds of H. peploides were grown for karyotyping using the enzymatic root tip squash method. Results from Seltjarnarnes samples show a tetraploid genome containing 68 metacentric and sub-metacentric chromosomes, two of ...